Computational fluid dynamics simulation of blood flow profile and shear stresses in bileaflet mechanical heart valve by using monolithic approach - Kadhim, S.K. (SAGE Publications Ltd, 2018)
Bileaflet mechanical heart valves (BMHVs) are widely used to replace diseased heart valves. However, patients may suffer from implant complications, such as platelet aggregation and damage to blood cells, which could lead to BMHV failure. These complications are related to the blood flow patterns in the BMHV. A three-dimensional computational fluid dynamic (CFD) model was developed to investigate blood hydrodynamics and shear stresses at different cardiac cycles. A user-defined function (UDF) code was developed to model the valve leaflet motion. This UDF updates the tetrahedral mesh according to the location of the valve leaflet, which enables modeling of complicated moving geometries and achieves solution convergence with ease without the need to adjust the relaxation factor values. The agreement between the experimental and numerical results indicates that the developed model could be used with confidence to simulate BMHV motion and blood flow. Furthermore, valve leaflet and valve pivot were found to be continuously exposed to shear stresses higher than 52.3 Pa which according to previous research findings may cause damage to blood platelets. Â© 2017, Â© The Author(s) 2017.